The efficacy of repetitive transcranial magnetic stimulation for Parkinson disease patients with depression. (2nd January 2020) - Hai-jiao, Wang; Ge, Tan; Li-na, Zhu; Deng, Chen; Da, Xu; Shan-Shan, Chu; Liu, Ling
Abstract: Objective: To evaluate the efficacy of repetitive transcranial magnetic stimulation for Parkinson disease (PD) patients with depression. Methods: A meta-analysis was performed using relevant randomized controlled trials (RCTs) from online databases such as PubMed, Embase, Cochrane Online Library, and Clinicaltrials.gov. Studies were selected according to pre-defined inclusion and exclusion criteria, and the quality of the studies was evaluated using the Jadad Scale. All data were pooled by RevMan 5.2 software for meta-analysis. Results: The review covered 528 articles, and 7 articles with Jadad score ≥4 were included in the analysis. The meta-analysis showed that, compared to sham repetitive transcranial magnetic stimulation (sham-rTMS), repetitive transcranial magnetic stimulation (rTMS) over dorsolateral prefrontal cortex (DLPFC) improved depression, but that there was no significant difference in depression improvement between rTMS and selective serotonin reuptake inhibitor (SSRI) treatment. In contrast, rTMS over DLPFC did not improve motor function compared to sham-rTMS or SSRI, and the studies that included neurocognitive measures showed no significant difference between rTMS and sham-rTMS. Conclusion: This meta-analysis provides evidence that rTMS over DLPFC can improve depression similar to SSRI treatment, has no effect on the motor function and cognition of PD patients with depression.